The true Christian life : thomistic reflections on divinization, prudence, religion, and prayer - Gardeil, A. (Ambroise), 1859-1931 (The Catholic University of America Press, 2022)
"The True Christian Life provides an introduction to the spiritual theology of a mid-20th century Thomistic master. The volume was originally published posthumously through the collaboration between Jacques Maritain and Fr. Ambroise Gardeil's nephew, Fr. Henri-Dominique Gardeil, OP. Fr. Ambroise, prior to beginning work on his masterpiece on spiritual experience, La Structure de l'âme et l'expérience mystique, drafted nearly eight-hundred pages that would have set forth a full presentation of moral-ascetical theology. Soon after his death, his nephew gathered several essays from the Revue thomiste and Revue des Jeunes, along with a complete-but-unpublished study on prayer. Fr. Henri-Dominique thus assembled this volume of moral / spiritual theology that sets out the principles of many important themes: divinization through grace, Christian prudence /conscience, the virtue of religion, devotion, and prayer"--